An FFRCT diagnostic strategy versus usual care in patients with suspected coronary artery disease planned for invasive coronary angiography at German sites: one-year results of a subgroup analysis of the PLATFORM (Prospective Longitudinal Trial of FFRCT: Outcome and Resource Impacts) study. Issue 1 (22nd March 2017) - Colleran, Roisin; Douglas, Pamela S; Hadamitzky, Martin; Gutberlet, Matthias; Lehmkuhl, Lukas; Foldyna, Borek; Woinke, Michael; Hink, Ulrich; Nadjiri, Jonathan; Wilk, Alan; Wang, Furong; Pontone, Gianluca; et al.
Abstract : Aim: Diagnostic evaluation practices for suspected coronary artery disease (CAD) may vary between countries. Our objective was to compare a CT-derived fractional flow reserve (FFRCT ) diagnostic strategy with usual care in patients with planned invasive coronary angiography (ICA) enrolled in the PLATFORM (Prospective Longitudinal Trial of FFRCT : Outcome and Resource Impacts) study at German sites. Methods: Patients were divided into two consecutive observational cohorts, receiving either usual care or CT angiography (CTA)/FFRCT . The primary endpoint was the percentage of patients planned for ICA, with no obstructive CAD on ICA within 90 days. Secondary endpoints included death, myocardial infarction, unstable angina, hospitalisation leading to unplanned revascularisation, cumulative radiation exposure, estimated medical costs and quality of life (QOL) at 1 year. Results: 116 patients were included. The primary endpoint occurred in 4 of the 52 patients (7.7%) in the CTA/FFRCT group and in 55 of the 64 patients (85.9%) in the usual care group (risk difference 78.2%, 95% CI 67.1% to 89.4%, p<0.001). ICA was cancelled in 40 of the 52 patients (77%) who underwent CTA/FFRCT . Clinical event rates were low overall. The mean radiation exposure was lower in the FFRCT versus the usual care group (7.28 vs 9.80 mSv, p<0.001). Mean estimated medical costs were €4217 (CTA/FFRCT ) versus €6894 (usual care), p<0.001. Improvement in QOL (EQ-5D score) was greater in the FFRCT (+0.09 units) versus the usual care cohort (+0.03 units), p=0.04. Conclusions: In patients with suspected CAD planned for ICA at German sites, initial CTA/FFRCT compared with usual care was associated with a markedly reduced rate of ICA showing no obstructive CAD, lower cumulative radiation exposure and estimated costs and greater improvement in QOL.